2012
DOI: 10.3126/njog.v6i2.6752
|View full text |Cite
|
Sign up to set email alerts
|

Hyperemesis Gravidarum and Obstetric Outcome

Abstract: Aims: This study was conducted to evaluate maternal characteristics and obstetric outcomes among women with hyperemesis gravidarum during pregnancy. Methods: A prospective hospital based study was conducted at Nepal medical college and teaching hospital over the period of two years where all the women admitted with history of hyperemesis gravidarum were evaluated. Hyperemesis gravidarum was defined as intractable nausea/vomiting in pregnancy that leads to dehydration, nutritional deficiency, electrolyte and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…14 In another study done in Nepal by Giri et al the condition was seen at gestational age of 5-7 weeks in 50% of the patients which is lower in comparision to our study findings. 4 In our study, 43 (74.3%) multigravida had history of hyperemesis in their previous pregnancy. However, in the study conducted by Chhetry et al found that previous history of HG was 16 (24%).…”
Section: Percentagementioning
confidence: 48%
See 3 more Smart Citations
“…14 In another study done in Nepal by Giri et al the condition was seen at gestational age of 5-7 weeks in 50% of the patients which is lower in comparision to our study findings. 4 In our study, 43 (74.3%) multigravida had history of hyperemesis in their previous pregnancy. However, in the study conducted by Chhetry et al found that previous history of HG was 16 (24%).…”
Section: Percentagementioning
confidence: 48%
“…1 In study done by Giri et al the mean hospital stay was 2.26 days and the range being 1-10 days. 4 The mean number of hospital stay in the study done by Konikoff et al was 2.24±2.2. 16 In a large cohort study done on elective termination of pregnancy done by Poursharif et al 123 women (15.2%) reported at least one elective termination of pregnancy due to HG.…”
Section: Percentagementioning
confidence: 83%
See 2 more Smart Citations
“… 66 Also, a study conducted in Nepal showed the association of preterm babies and HG. 67 HG has different physiological consequences for the mother, such as dehydration, electrolyte imbalances, and severe loss of weight, as well as concern about the effects of babies. 68 …”
Section: Discussionmentioning
confidence: 99%